Estimating Contact Rates Between Metarhizium anisopliae–Exposed Males With Female Aedes aegypti - Reyes-Villanueva, Filiberto; Russell, Tanya L.; Rodríguez-Pérez, Mario A. (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction: Effective control of Aedes aegypti will reduce the frequency and severity of outbreaks of dengue, chikungunya and Zika, however control programs are increasingly threatened by the rapid development of insecticide resistance. Thus there is an urgent need for novel vector control tools, such as auto-dissemination of the entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana. The aim of this study was to estimate contact rates of M. anisopliae-exposed males with wild female Ae. aegypti. As a control the contact rates of untreated males with wild females was contrasted. Methods: The study was conducted in Reynosa, Mexico. The treatment and control households (n = 15 per group) were geographically separated by an arid and hot area that naturally prevented the flight of males between arms. In each control household, 40 M. anisopliae-exposed male Ae. aegypti were released per week for 8 weeks (specimens were exposed to a concentration of 5.96 x 107 conidia cm2 for 24 hours; n = 4,800 males). In each control household, 40 untreated males were released per week for 8 weeks (n = 4,800 males). All specimens were dust-marked prior to release. Mosquito abundance was monitored with human landing collections, and captured Ae. aegypti were examined for any dust-marking. Results: In the treatment households, the contact rate of Ae. aegypti females with marked, fungus-treated males was 14% (n = 29 females marked from 197). Where in the control households, the contact rate of females with marked, untreated males was only 6% (n = 22 marked from 365). In the treatment households the recapture rate of released males was at 5% and higher than that for the control households (which was 2%). Auto-dissemination of M. anisopliae from infected males to female Ae. aegypti was demonstrated through the recovery of an infected female from the floor of a household. Conclusions: Overall, the contact rate between M. anisopliae-infected males with the natural female population was 60% higher than for the control group of healthy males. The results provide further support to the release of fungus-exposed males as a potentially useful strategy against Ae. aegypti, though further research is required.